Analisis Electron Beam Output Constancy pada Pesawat Linear Accelelator (LINAC) Elekta Precise di Instalasi Radioterapi RSUP Sanglah Denpasar - Made Aditya Jaya Mahardika; Ni Nyoman Ratini; I Wayan Balik Sudarsana; Fitriyani Mus Mulyadi (Universitas Hamzanwadi, 2022)
An analysis of the electron beam output constancy has been conducted on the Elekta Precise Linear Accelerator (LINAC) aircraft at the Radiotherapy Installation at Sanglah Hospital, Denpasar. The energy variations used are 8 MeV and 10 MeV. The analysis of the electron beam output constancy is determined by the standard deviation value obtained. The results of this study were obtained at an energy of 8 MeV with a large deviation value of 0.083% - 1.041%, and an energy of 10 MeV with a large deviation value of 0.022% - 0.695%. Based on the calculation results that the deviation value is still below the tolerance limit set by the AAPM. So that the LINAC Elekta Precise aircraft at the Radiotherapy Installation at Sanglah Hospital Denpasar is suitable to operate to receive patients.